Pengembangan Mobile-Assisted Language Learning Menggunakan User Centered Design - Manda Rohandi; Nurlaila Husain; Indri W. Bay (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
This paper aims to develop a mobile-assisted language learning (MALL) application for English intensive course (EIC) using user centered design method. This method consists of four steps: 1) specify context of use; 2) specify user and organizational requirements; 3) produce design solution; and 4) evaluate design against user. The result shows that users (students) feel that the MALL application can help the students to study and comprehend the EIC material. Students can use the MALL application for self-study, inside and outside the classroom, whether in idle or mobile. For the lecturers, the MALL application is very helpful in teaching and learning process.